Prevalence of lesions associated with subclinical laminitis in dairy cattle - Sagliyan, A.; Gunay, C.; Han, M.C. (My University, 2010)
Lameness is an important cause of reduced animal welfare and has been shown to cause substantial economical losses in dairy and beef-cattle herds. Lameness is perhaps one of the most important diseases of the modern dairy cow. Laminitis is a diffuse aseptic inflammation of the laminar corium of the hoof wall and, in the bovine definition, also includes the sole corium. There are various forms of laminitis: subclinical, acute or subacute, and chronic. Subclinical laminitis is the most common form of laminitis in dairy cows. For the study, we aimed to determine the prevalance of the lesions associated with subclinical laminitis in 1352 dairy cows from 132 cow barns in Elazig province between 2007 and 2008. Of the 1352 cows selected for the study, lameness was detected in 387 (28.6%). Of these lame cows, 320 (82.7%) had 591 lesions that could be associated with subclinical laminitis. Claw lesions were diagnosed on the basis of macroscopic examination before and after trimming to the correct claw shape. In this study, yellow discolouration and haemorrhage of the white line and the sole, separation of the white line, erosion of the heel, double sole, sole ulcers, flaky or chalky white powder on the sole, abscessed soles were considered lesions associated with subclinical laminitis. The most common lesions were separation of the white line (20.98%) and haemorrhage of the sole (20.31%). Consequently, in this study, it was found that causes of 82.7% of lameness showed in cattle in Elazig region was originated from subclinical laminitis-related lesions.
Keywords: Dairy cattle; Prevalence; Subclinical laminitis